Occupational Safety and Health Analysis in the COVID-19 Pandemic - Marcin OLKIEWICZ; Igor POGONOWSKI (Communications of International Proceedings, 2022)
The growing sense of lack of occupational health and safety of employees during the Covid-19 pandemic forces organizations to implement various types of changes. The safety of the workplace, employees and customers of micro-enterprises is so important because it has a significant impact on the proper functioning and development of business entities. The purpose of the publication is to identify and evaluate activities in the field of dealing with COVID-19 by micro-enterprises. The analysis of the literature indicates a limited amount of research in this area, and the lack of such analyzes (data) concerns Polish micro-enterprises from the Central Pomeranian region. The results of the survey conducted in 2021 show that as many as 68% of the surveyed entities were negatively affected by the COVID-19 pandemic. The presented research results indicate that, depending on the type of activity, as well as legal epidemic restrictions, micro-enterprises increased the safety of employees and customers in different ways and using different tools during the COVID-19 pandemic, e.g. by using gels or liquids for disinfecting hands and surfaces working hours (88%); regular cleaning and disinfection of equipment and workstations (83%); maintaining social distance (76%). However, despite the use by organizations of a number of safeguards to increase occupational health and safety, the level of feeling remained almost at the same level (a decrease of 3 percentage points). The results indicate the need to expand and deepen research activities, e.g. by examining the economic effects and profitability of the implemented changes (e.g. remote work).
Keywords: COVID-19; safty; microenterprises; occupational health and safety